Dampak Oforektomi terhadap Kualitas Hidup dan Fungsi Seksual Orang dengan Kanker Payudara - Fuadi, Hasan; Afiyanti, Yati; Gayatri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the impact of orthorectomy on breast cancer patients, especially on their quality of life and sexual function. We conducted a systematic review adhering to PRISMA guidelines, searching articles from PubMed, ProQuest, Embase, and ScienceDirect databases from inception to March 2024. The search terms used were